Study the Effect of Tapered Channel on the Flow Over Side Weir - Ayat Mehdi Kadhim; Faisal Abdulrazak Majid (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Weir is usually used in different hydraulic purpose, and mainly for head the discharge water relationship in channel. In this research the flow has been carried out over horizontal side weir (θ=0˚) with a constant crest length and height 15 cm, 5 cm respectively. The tapering part of the channel designed to be 15 cm length and have five values in narrowing of the channel widths. The tapered channel is started with a width of 20 cm, and terminated with a width of 18 cm, 16 cm, 14 cm, 12 cm and 10 cm consequently. The discharge over side weir increase with increasing the degree of constriction, the discharge reach to the maximum value at the highest degrees of constriction. When the construction of tapered channel increase the discharge over the side weir increase as the same time the height of water after side weir increase, that maybe use to supply another sub- channel with water. The water surface profile along the side weir is studied and taken under consideration for side weir and tail weir. The ANSYS program was used to calculate the discharge value over side and tail weir of the channel and compare this result with those calculated theoretically from laboratory work result. ANSYS program also used to show the surface water profile over side and tail weir in all cases of constriction. The water surface a long side weir is stable and close to the straight line in most cases, except the surface profile over tail weir for the last three cases of constriction (20-14) cm, (20-12) cm and (20-10) cm, the shape of water surface will be disturbed and unsteady. The purpose of this study to know the effect of changing the transition section channel on the discharge over the side weir with applying spatially varied flow theories over the weir crest, the effect of the flow velocity in the main channel on the discharge coefficient of the side weir according to tangential and radial flow across the channel and the discharge value and water surface profile a long side weir and tail weir from ANSYS software and compare them with the results that obtained from laboratory work.